Abnormal liquor volume and mode of delivery (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Sonographic assessment of four quadrant measurement of amniotic fluid index (AFI) is an integral part of antenatal evaluation of pregnancies, especially in the third trimester. Decreased (oligohydramnios, AFI 0-9.9 cm) or increased (polyhydramnios >25 cm) increases the risk of intrauterine growth retardation, birth asphyxia and induction or operative interference. The aim of this study was to analyse abnormal liquor volume and mode of delivery.Methods: This retrospective cross-sectional study analysed the cases of abnormal liquor volume in term pregnancies during 2013-2016 at Patan Hospital. Patient's files were traced from medical record section. We analysed the abnormal liquor volume based on amniotic fluid index (AFI) and the mode of deliveries.Results: Among 15,272 term pregnancies scanned, 130 had abnormal AFI, 128 oligohydramnios and 2 polyhydramnios. Out of 128 oligohydramnios, 40 (30.8%) were severe, 54 (41.5%) moderate and 34 (26.2%) mild. Two cases had polyhydramnios. The emergency lower uterine segment caesarean sections (emLSCS) were performed in 99 (76.1%) oligohydramnios.Conclusions: This study suggests that oligohydramnios measured by AFI at term pregnancy required more emLSCS.